1975
DOI: 10.1212/wnl.25.2.150
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic dysfunction in botulism B

Abstract: Nine cases of botulism B with preponderant effects upon cholinergic autonomic innervation are presented. Blurred vision and dry mouth were constant symptoms. Impairment of salivary and lacrimal secretion were detectable for months. In the absence of clinical signs, electromyographic studies did not reveal neuromuscular involvement. Administration of antitoxin in the late course of such cases is not recommended, but guanidine can be used. Doubt is cast upon a new clinical entity called "acute autonomic neuropat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0
1

Year Published

1978
1978
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(22 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…Clinically, this presents with mydriasis, accommodation paresis, delayed pupillary reaction to light, reduced saliva secretion and lacrimation, constipation, disturbed micturition and cardiovascular regulation [18,25]. Autonomic dysfunction has also been shown to result from experimental injections of botulinum toxin [1] and was noted as a side-effect of treatment with botulinum toxin [4,12,20].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, this presents with mydriasis, accommodation paresis, delayed pupillary reaction to light, reduced saliva secretion and lacrimation, constipation, disturbed micturition and cardiovascular regulation [18,25]. Autonomic dysfunction has also been shown to result from experimental injections of botulinum toxin [1] and was noted as a side-effect of treatment with botulinum toxin [4,12,20].…”
Section: Introductionmentioning
confidence: 99%
“…Recovery of muscle function usually requires 2-4 months and occurs through several mechanisms most importantly, neural sprouting and reinnervation [11]. Botulinum toxin, especially type B toxin, also has autonomic effects [12], due to the alterations in peripheral cholinergic parasympathetic nerves. This effect can be used to reduce tear production in lacrimal hypersecretion [13,14].…”
mentioning
confidence: 99%
“…In 1975, Jenzer et al [4] reported blurred vision, dry mouth, and constipation to be the most frequent and consistent symptoms. A botulinum toxin induced delayed gastrointestinal transit may be an important factor determining the severity of the intoxication as it might increase the bioavailability of the toxin.…”
Section: Discussionmentioning
confidence: 99%
“…A botulinum toxin induced delayed gastrointestinal transit may be an important factor determining the severity of the intoxication as it might increase the bioavailability of the toxin. Sexual dysfunction has only been mentioned in a single case [4]. Botulism may therefore be an underestimated cause of pure autonomic dysfunction.…”
Section: Discussionmentioning
confidence: 99%